2009
DOI: 10.4315/0362-028x-72.2.325
|View full text |Cite
|
Sign up to set email alerts
|

Antipathogenic Properties of Green Tea Polyphenol Epigallocatechin Gallate at Concentrations below the MIC against Enterohemorrhagic Escherichia coli O157:H7

Abstract: The inhibitory effects of green tea polyphenol epigallocatechin gallate (EGCG) on virulence phenotypes and gene expression regulated by quorum sensing (QS) in Escherichia coli O157:H7 were demonstrated at concentrations of 1 to 100 microg/ml, which are lower than the MIC (539 +/- 22 microg/ml). At 25 microg/ml, the growth rate was not affected, but autoinducer 2 concentration, biofilm formation, and swarm motility decreased to 13.2, 11.8, and 50%, respectively. Survival at 5 days of nematodes (Caenorhabditis e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 35 publications
3
39
0
Order By: Relevance
“…In light of the reported adverse effects of antibiotic use in human E. coli O157:H7 infections, investigations into therapeutic modes have focused on the use of natural products and have ranged from testing green tea components [33] to more recently American cranberry constituents [34]. However, these studies were mostly performed at the in vitro level.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the reported adverse effects of antibiotic use in human E. coli O157:H7 infections, investigations into therapeutic modes have focused on the use of natural products and have ranged from testing green tea components [33] to more recently American cranberry constituents [34]. However, these studies were mostly performed at the in vitro level.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a decrease in toxin production has been reported following treatment with plant extracts such as catechin [100], epigallocatechin [101], cinnamon bark oil, cinnamaldehyde, and eugenol [102]. In addition, plant extracts, including green tea extracts, tea catechins, and green tea polyphenol were found to modulate other virulence attributes in EHEC such as biofilm formation, swarming motility and quorum sensing [103]. Since the concentrations of plant compounds used in above studies were below MIC, the effects observed were not due to reduction in cell number, but probably due to modulation of gene transcription in cells.…”
Section: Studies Highlighting the Anti-toxin Properties Of Plant-dmentioning
confidence: 99%
“…Although the suppression of transcriptional levels of various quorumsensing-regulated virulence genes by EGCg has been reported in Escherichia coli 0157:H7 (Lee et al, 2009) Figure 4. Effects of increasing concentrations of EGCg on METase protein expression in P. gingivalis W83.…”
Section: Acknowledgmentsmentioning
confidence: 99%